Method of producing lithium metal composite oxide and metal composite hydroxide powder
By calcine treatment of metal composite hydroxide powder and lithium source substance at a specific temperature, lithium metal composite oxides with high cycle stability and large battery capacity were prepared, which solved the problem of crystal structure instability of lithium-ion secondary batteries during cyclic charging and discharging and high-temperature storage in the prior art.
Patent Information
- Application Number
- JP2023163691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-08
AI Technical Summary
In the prior art, the crystal structure of lithium metal composite oxide is unstable during the cycle charging and discharging process, resulting in a decrease in the battery capacity of the lithium-ion secondary battery, and the same problem exists when storing in a high-temperature environment.
By calculating the metal composite hydroxide powder and the lithium source substance between 700°C and 950°C, lithium metal composite oxides containing at least nickel are prepared, and technologies such as scanning electron microscopy are used to ensure that the particle size and shape meet specific requirements.
The high stability and large battery capacity of lithium-ion secondary batteries during the cycle charging and discharging process are achieved, reducing the expansion and contraction of the crystal structure, and improving the cycling performance and high-temperature storage capabilities of the battery.
Smart Images

Figure 2025054574000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a lithium metal composite oxide and a metal composite hydroxide powder. [Background technology]
[0002] In recent years, portable and cordless electronic devices such as mobile phones and notebook computers have rapidly become widespread, and non-aqueous secondary batteries that are small, lightweight, and have high energy density are used as power sources for these devices. Among these, lithium-ion secondary batteries that use lithium metal composite oxides such as lithium cobalt oxide and lithium nickel oxide in the positive electrode are widely used.
[0003] Lithium cobalt oxide is an excellent material with high voltage and high capacity, and is indispensable as a positive electrode material for small electronic devices. However, it has a problem of high cost because it is made from rare and expensive cobalt compounds.
[0004] In recent years, therefore, there has been active research into ternary positive electrode active material particles (basic composition Li(NiCoMn)O2) with a layered rock salt structure, which is a versatile solid solution of Ni, Co, and Mn, and lithium-nickel composite compounds (basic composition Li(NiCoAl)O2) that introduce Al into lithium nickel oxide and reduce the amount of cobalt used.
[0005] Future positive electrode materials are expected to exhibit high battery voltages similar to lithium-cobalt composite oxides, as well as large charge / discharge capacities, making it possible to expand the range of applications of lithium-ion secondary batteries to include electric vehicles and stationary storage batteries, and further research and development is being actively conducted.
[0006] However, the capacity of lithium-ion secondary batteries decreases when they are repeatedly charged and discharged or stored in a charged state in a high-temperature environment. This is thought to be due to the fact that the layered rock-salt structure of the positive electrode material changes in crystal structure and expands and contracts due to repeated charging and discharging or depending on the charging state.
[0007] In order to achieve high stability in lithium ion secondary batteries, it is considered important to suppress the destabilization of the crystal structure, particularly in lithium nickel composite oxides. To achieve this, various methods have been adopted, including controlling the composition balance, crystallite size, and particle size distribution, controlling the firing temperature to obtain powder, adding different elements to strengthen the bonding strength in the crystal structure, and preventing the destruction of the structure by surface treatment or the reaction from the electrolyte.
[0008] For example, Patent Document 1 proposes a lithium metal composite oxide having a basic composition of LiMO2, where M is a group of four or more elements including at least three elements selected from Co, Mn, Al, Mg, and Ti, and Ni. Patent Document 1 reports that in a lithium-containing composite oxide, by substituting Al for the metal site and substituting Mg for the metal site and Li site, the expansion and contraction rate of the crystal structure due to the insertion and removal of Li during charging and discharging can be reduced, and as a result, irreversible reactions can be alleviated, thereby improving cycle characteristics. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2011-023335 A Summary of the Invention [Problem to be solved by the invention]
[0010] However, the lithium metal composite oxide described in Patent Document 1 does not have sufficient cycle characteristics for practical use, and there is still room for improvement.
[0011] The present disclosure has been made in consideration of the above-mentioned circumstances, and has an object to provide a method for producing a lithium metal composite oxide that, when used as a positive electrode active material, causes a nonaqueous electrolyte secondary battery using the same to exhibit high cycle characteristics and charge / discharge capacity, and a metal composite hydroxide used in the production thereof. [Means for solving the problem]
[0012] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, it has been found that a lithium metal composite hydroxide produced by a production method including a step of baking a mixture of a metal composite hydroxide powder and a lithium source at 700° C. or more and 950° C. or less, the metal composite hydroxide powder contains at least nickel and contains secondary particles formed by aggregation of primary particles, and when the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more in a backscattered electron image of a cross section obtained using a scanning electron microscope, and the volume of pores having a pore diameter of 0.06 μm or less is 0.15 mL / g or less, can provide a method for producing a lithium metal composite oxide, and a metal composite hydroxide used for the production, in which a nonaqueous electrolyte secondary battery using the lithium metal composite hydroxide as a positive electrode active material exhibits high cycle characteristics and charge / discharge capacity. Specifically, the present disclosure provides the following.
[0013] (1) comprising a step of calcining a mixture of a metal composite hydroxide powder and a lithium source at 700° C. or more and 950° C. or less; The metal composite hydroxide powder contains at least nickel and includes secondary particles formed by aggregation of primary particles, When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more by number of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more that account for 10% or more by number in a backscattered electron image of a cross section obtained using a scanning electron microscope; The pore volume of pores with diameters of 0.06 μm or less is 0.15 mL / g or less A method for producing a lithium metal composite oxide.
[0014] (2) calcining the metal composite hydroxide powder at 200° C. or more and less than 700° C. to obtain a calcined product; sintering the mixture of the calcined product and the lithium source at a temperature of 700° C. or higher and 950° C. or lower; The metal composite hydroxide powder contains at least nickel and includes secondary particles formed by aggregation of primary particles, When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more by number of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more that account for 10% or more by number in a backscattered electron image of a cross section obtained using a scanning electron microscope; The pore volume of pores with diameters of 0.06 μm or less is 0.15 mL / g or less A method for producing a lithium metal composite oxide.
[0015] (3) The metal composite hydroxide powder has the general formula Ni 1-x-y-z Co x Mn y M z (OH) 2+α (wherein M is an element other than Li, Ni, Co, Mn, and O, and 0≦x≦0.4, 0≦y≦0.4, 0≦z≦0.1, and −0.5≦α≦0.5).
[0016] (4) A method for producing a lithium metal composite oxide according to (1) or (2), in which 30% or more by number of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 2 μm or more in a backscattered electron image of a cross section obtained using a scanning electron microscope.
[0017] (5) The BET specific surface area of the metal composite hydroxide powder is 1 m 2 / g or more 15m 2 / g or less.
[0018] (6) Contains at least nickel and includes secondary particles formed by agglomeration of primary particles; When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are, on a number basis, primary particles having a major axis length of 1 μm or more in a backscattered electron image of a cross section obtained using a scanning electron microscope, and The pore volume of pores with diameters of 0.06 μm or less is 0.15 mL / g or less Metal composite hydroxide powder. Effect of the Invention
[0019] According to the present disclosure, it is possible to provide a method for producing a lithium metal composite oxide that, when used as a positive electrode active material, causes a nonaqueous electrolyte secondary battery using the same to exhibit high cycle characteristics and charge / discharge capacity, and a metal composite hydroxide used in the production thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, embodiments of the present disclosure will be described, however, the present disclosure is not limited in any way to the description of the embodiments and can be implemented with appropriate modifications.
[0021] <Method for producing lithium metal composite oxide> The method for producing a lithium metal composite oxide according to the first embodiment of the present disclosure includes a step of calcining a mixture of a metal composite hydroxide powder and a lithium source at 700° C. or more and 950° C. or less (calcination step). In the method for producing a lithium metal composite oxide according to the first embodiment of the present disclosure, the metal composite hydroxide powder contains at least nickel and includes secondary particles formed by aggregation of primary particles, and when the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more by number of secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more that account for 10% or more by number in a backscattered electron image of a cross section obtained using a scanning electron microscope, and the volume of pores having a pore diameter of 0.06 μm or less is 0.15 mL / g or less.
[0022] A method for producing a lithium metal composite oxide according to a second embodiment of the present disclosure includes a step of calcining a metal composite hydroxide powder at 200° C. or more and less than 700° C. to obtain a calcined product (calcination step), and a step of calcining a mixture of the calcined product and a lithium source at 700° C. or more and 950° C. or less (calcination step). In the method for producing a lithium metal composite oxide according to the second embodiment of the present disclosure, the metal composite hydroxide powder contains at least nickel and contains secondary particles formed by aggregation of primary particles, and when the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more by number, and the volume of pores having a pore diameter of 0.06 μm or less is 0.15 mL / g or less, where Dt is the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles.
[0023] According to the method for producing a lithium metal composite oxide according to an embodiment of the present disclosure, it is possible to produce a lithium metal composite oxide that, when used as a positive electrode active material, causes a nonaqueous electrolyte secondary battery using the same to exhibit high cycle characteristics and charge / discharge capacity.
[0024] Hereinafter, an example of a method for producing a lithium metal composite oxide according to an embodiment of the present disclosure will be described step by step. Specifically, the example of a method for producing a lithium metal composite oxide according to an embodiment of the present disclosure includes the following steps (1) to (6).
[0025] (1) Precursor preparation step: If necessary, a metal composite hydroxide (precursor material) containing at least nickel is prepared. (2) Calcination step: If necessary, the metal composite hydroxide powder is calcined. (3) Mixing step: If necessary, the metal composite hydroxide powder prepared in the precursor preparation step and / or the calcined product prepared in the calcination step are mixed with a lithium compound to prepare a mixture. (4) Firing step: The mixture prepared in the mixing step is fired. (5) Washing step: If necessary, the lithium metal composite oxide obtained by firing in the firing step is subjected to a water washing treatment. (6) Surface treatment step: If necessary, the lithium metal composite oxide obtained in the firing step or washing step is subjected to a surface treatment.
[0026] (1) Precursor Preparation Step In the raw material preparation step, a metal composite hydroxide is synthesized as an aggregate of primary particles of the lithium metal composite oxide. Note that the precursor preparation step is not an essential step in the method for producing a lithium metal composite oxide according to the embodiment of the present disclosure.
[0027] (Characteristics of metal composite hydroxide powder) Here, the metal composite hydroxide powder used in the manufacturing method of a lithium metal composite oxide according to an embodiment of the present disclosure (i.e., prepared in this step) contains at least nickel, and includes secondary particles formed by aggregation of primary particles, and when the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more by number of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more that account for 10% or more by number in a backscattered electron image of a cross-section obtained using a scanning electron microscope, and the pore volume of pores with diameters of 0.06 μm or less is 0.15 mL / g or less.
[0028] Such a metal composite hydroxide powder has particles that have grown to a length of 1 μm or more in at least one direction when viewed from the cross section of the secondary particle. Since the primary particles of the metal composite hydroxide powder tend to grow in a plate shape, it is sufficient to selectively grow them in a direction perpendicular to the flat plate surface. Specifically, in the above manufacturing method, the production of the metal composite hydroxide powder is divided into a nucleation stage and a crystallization stage, and conditions are selected in the nucleation stage so that the generated nuclei do not grow too much, and conditions are selected in the crystallization process so that the nuclei selectively grow in a direction perpendicular to the flat plate surface. Note that the conditions of the nucleation stage and the crystallization stage may change depending on the element composition constituting the metal composite hydroxide powder and the mutual relationship between the conditions of the nucleation stage and the crystallization stage, but the metal composite hydroxide powder according to the embodiment of the present disclosure can be manufactured at least under the conditions of the examples described below.
[0029] The inventors have surprisingly found that a lithium metal composite oxide obtained by calcining such a metal composite hydroxide powder exhibits high cycle characteristics and charge / discharge capacity when used in a non-aqueous electrolyte secondary battery. The reason for this is not entirely clear, but the inventors believe it to be as follows. The above-mentioned metal composite hydroxide powder has voids inside the secondary particles. These spaces are maintained at an appropriate size even after being calcined and transformed into a lithium metal composite oxide, and absorb the volume expansion and contraction caused by the charging and discharging of lithium, which is thought to result in the high cycle characteristics.
[0030] The chemical composition of the metal composite hydroxide contained in the metal composite hydroxide powder is not particularly limited as long as it contains nickel. For example, the metal composite hydroxide may be represented by the general formula: 1-x-y-z Co x Mn y M z (OH) 2+α (wherein M is an element other than Li, Ni, Co, Mn and O, and 0≦x≦0.4, 0≦y≦0.4, 0≦z≦0.1, and −0.5≦α≦0.5).
[0031] In the general formula, the value of x is not particularly limited as long as it is within the range of 0≦x≦0.4, and examples thereof include: more than 0, 0.001 or more, 0.0015 or more, 0.002 or more, 0.0025 or more, 0.003 or more, 0.0035 or more, 0.004 or more, 0.0045 or more, 0.005 or more, 0.0055 or more, 0.006 or more, 0.0065 or more, 0.007 or more, 0.0075 or more, 0.008 or more, 0.0085 or more, 0.009 or more, 0.0095 or more, 0.01 or more, 0.015 or more, 0.02 or more, 0.025 or more, 0.03 or more, 0.035 or more, 0.04 or more, 0.045 or more, 0.05 or more, 0.055 or more, 0.06 or more, 0.065 or more, 0.07 or more, 0.075 or more, 0.08 or more, 0.085 or more, 0.09 or more, 0.095 or more, 0.1 or more, 0.102 or more, 0.105 or more, 0.107 or more, 0.11 or more, 0.112 or more, 0.115 or more, 0.117 or more, 0.12 or more, 0.122 or more, 0.125 or more, 0.127 or more, 0.13 or more, 0.132 or more, 0.135 or more, 0.137 or more, 0.14 or more, 0.142 or more, 0.145 or more, 0.147 or more, 0.15 or more, 0.152 or more, 0.155 or more, 0.157 or more, 0.16 or more, 0.162 or more, 0.165 or more, 0.167 or more, 0.17 or more, 0.172 or more, 0.175 or more, 0.177 or more, 0.18 or more, 0.182 or more, 0.185 or more, 0.187 or more, 0.19 or more, 0.192 or more, 0.195 or more, 0.197 or more, 0.2 or more, 0.202 or more, 0.205 or more, 0.207 or more, 0.21 or more, 0.212 or more, 0.215 or more, 0.217 or more, 0.22 or more, 0.222 or more, 0.225 or more, 0.227 or more, 0.23 or more, 0.232 or more ,0.235 or more,0.237 or more,0.24 or more,0.242 or more,0.245 or more,0.247 or more,0.25 or more,0.252 or more,0.255 or more,0.257 or more,0.26 or more,0.262 or more,0.265 or more,0.267 or more,0.27 or more,0.272 or more,0.275 or more,0.277 or more,0.28 or more,0.282 or more,0.285 or more,0.287 or more,0.29 or more,0.292 or more,0.295 or more,0.297 or more,0.3 or more,0.302 or more,0.305 or more,0.307 or more,0.31 or more,0.312 or more,0.It is preferable that the molecular weight is 315 or more, 0.317 or more, 0.32 or more, 0.322 or more, 0.325 or more, 0.327 or more, 0.33 or more, 0.332 or more, 0.335 or more, 0.337 or more, 0.34 or more, 0.342 or more, 0.345 or more, 0.347 or more, 0.35 or more, 0.352 or more, 0.355 or more, 0.357 or more, 0.36 or more, 0.362 or more, 0.365 or more, 0.367 or more, 0.37 or more, 0.372 or more, 0.375 or more, 0.377 or more, 0.38 or more, 0.382 or more, 0.385 or more, 0.387 or more, 0.39 or more, 0.392 or more, 0.395 or more, or 0.397 or more. On the other hand, the values of x are 0.397 or less, 0.395 or less, 0.392 or less, 0.39 or less, 0.387 or less, 0.385 or less, 0.382 or less, 0.38 or less, 0.377 or less, 0.375 or less, 0 .372 or less, 0.367 or less, 0.365 or less, 0.362 or less, 0.36 or less, 0.357 or less, 0.355 or less, 0.352 or less, 0.35 or less, 0.347 or less, 0.345 or less, 0.342 or less Below, 0.34 or less, 0.337 or less, 0.335 or less, 0.332 or less, 0.33 or less, 0.327 or less, 0.325 or less, 0.322 or less, 0.32 or less, 0.317 or less, 0.315 or less, 0.3 12 or less, 0.31 or less, 0.307 or less, 0.305 or less, 0.302 or less, 0.3 or less, 0.297 or less, 0.295 or less, 0.292 or less, 0.29 or less, 0.287 or less, 0.285 or less, 0. 282 or less, 0.28 or less, 0.277 or less, 0.275 or less, 0.272 or less, 0.27 or less, 0.267 or less, 0.265 or less, 0.26 or less, 0.257 or less, 0.255 or less, 0.252 or less , 0.25 or less, 0.247 or less, 0.245 or less, 0.242 or less, 0.24 or less, 0.237 or less, 0.235 or less, 0.232 or less, 0.23 or less, 0.227 or less, 0.225 or less, 0.222 0.22 or less, 0.217 or less, 0.215 or less, 0.212 or less, 0.21 or less, 0.207 or less, 0.205 or less, 0.202 or less, 0.2 or less, 0.197 or less, 0.195 or less, 0.19 2 or less, 0.19 or less, 0.187 or less, 0.185 or less, 0.182 or less, 0.18 or less, 0.177 or less, 0.175 or less, 0.172 or less, 0.17 or less, 0.167 or less, 0.165 or less, 0.162 or less, 0.16 or less, 0.155 or less, 0.152 or less, 0.15 or less, 0.147 or less, 0.145 or less, 0.142 or less, 0.14 or less, 0.137 or less, 0.135 or less, 0.132 or less, 0.13 or less, 0.127 or less, 0.125 or less, 0.122 or less, 0.12 or less, 0.117 or less, 0.115 or less, 0.112 or less, 0.11 or less, 0.107 or less, 0.105 or less, 0.102 or less, 0.1 or less, 0.095 or less, 0.09 or less, 0.085 or less, 0.08 or less, 0.075 or less, 0.07 or less, 0.065 or less, 0 It is preferable that the ratio is 0.06 or less, 0.055 or less, 0.05 or less, 0.045 or less, 0.04 or less, 0.035 or less, 0.03 or less, 0.025 or less, 0.02 or less, 0.015 or less, 0.01 or less, 0.0095 or less, 0.009 or less, 0.0085 or less, 0.008 or less, 0.0075 or less, 0.007 or less, 0.0065 or less, 0.0055 or less, 0.005 or less, 0.0045 or less, 0.004 or less, 0.0035 or less, 0.003 or less, 0.0025 or less, 0.002 or less, 0.0015 or less, or 0.001 or less.
[0032] In the general formula, the value of y is not particularly limited as long as it is within the range of 0≦y≦0.4, and may be, for example, 0.001 or more, 0.0015 or more, 0.002 or more, 0.0025 or more, 0.003 or more, 0.0035 or more, 0.004 or more, 0.0045 or more, 0.005 or more, 0.0055 or more, 0.006 or more, 0.0065 or more, 0.007 or more, 0.0075 or more, 0.008 or more, 0.0085 or more, 0.009 or more, 0.0095 or more, 0.01 or more, 0.015 or more, 0.02 or more, 0.025 or more, 0.03 or more, 0.035 or more, 0.04 or more, 0. 045 or more, 0.05 or more, 0.055 or more, 0.06 or more, 0.065 or more, 0.07 or more, 0.075 or more, 0.08 or more, 0.085 or more, 0.09 or more, 0.095 or more, 0.1 or more, 0.102 or more, 0.105 or more, 0.107 or more, 0.11 or more, 0.112 or more, 0.115 or more, 0.117 or more, 0.12 or more, 0.122 or more, 0.125 or more, 0.127 or more, 0.13 or more, 0.132 or more, 0.135 or more, 0.137 or more, 0.14 or more, 0.142 or more, 0.145 or more, 0.147 or more, 0.15 or more, 0.152 or more ,0.155 or more,0.157 or more,0.16 or more,0.162 or more,0.165 or more,0.167 or more,0.17 or more,0.172 or more,0.175 or more,0.177 or more,0.18 or more,0.182 or more,0.185 or more,0.187 or more,0.19 or more,0.192 or more,0.195 or more,0.197 or more,0.2 or more,0.202 or more,0.205 or more,0.207 or more,0.21 or more,0.212 or more,0.215 or more,0.217 or more,0.22 or more,0.222 or more,0.225 or more,0.227 or more,0.23 or more, 0.235 or more, 0.237 or more, 0.24 or more, 0.242 or more, 0.245 or more, 0.247 or more, 0.25 or more, 0.252 or more, 0.255 or more, 0.257 or more, 0.26 or more, 0.262 or more, 0.265 or more, 0.267 or more, 0.27 or more, 0.272 or more, 0.275 or more, 0.277 or more, 0.282 or more, 0.285 or more, 0.287 or more, 0.29 or more, 0.292 or more, 0.295 or more, 0.297 or more, 0.3 or more, 0.302 or more, 0.305 or more, 0.307 or more, 0.31 or more, 0.312 or more, 0.It is preferable that the molecular weight is 315 or more, 0.317 or more, 0.32 or more, 0.322 or more, 0.325 or more, 0.327 or more, 0.33 or more, 0.332 or more, 0.335 or more, 0.337 or more, 0.34 or more, 0.342 or more, 0.345 or more, 0.347 or more, 0.35 or more, 0.352 or more, 0.355 or more, 0.357 or more, 0.36 or more, 0.362 or more, 0.365 or more, 0.367 or more, 0.37 or more, 0.372 or more, 0.375 or more, 0.377 or more, 0.38 or more, 0.382 or more, 0.385 or more, 0.387 or more, 0.39 or more, 0.392 or more, 0.395 or more, or 0.397 or more. On the other hand, the values of y are 0.397 or less, 0.395 or less, 0.392 or less, 0.39 or less, 0.387 or less, 0.385 or less, 0.382 or less, 0.38 or less, 0.377 or less, 0.375 or less, 0 .372 or less, 0.367 or less, 0.365 or less, 0.362 or less, 0.36 or less, 0.357 or less, 0.355 or less, 0.352 or less, 0.35 or less, 0.347 or less, 0.345 or less, 0.342 or less Below, 0.34 or less, 0.337 or less, 0.335 or less, 0.332 or less, 0.33 or less, 0.327 or less, 0.325 or less, 0.322 or less, 0.32 or less, 0.317 or less, 0.315 or less, 0.3 12 or less, 0.31 or less, 0.307 or less, 0.305 or less, 0.302 or less, 0.3 or less, 0.297 or less, 0.295 or less, 0.292 or less, 0.29 or less, 0.287 or less, 0.285 or less, 0. 282 or less, 0.28 or less, 0.277 or less, 0.275 or less, 0.272 or less, 0.27 or less, 0.267 or less, 0.265 or less, 0.26 or less, 0.257 or less, 0.255 or less, 0.252 or less , 0.25 or less, 0.247 or less, 0.245 or less, 0.242 or less, 0.24 or less, 0.237 or less, 0.235 or less, 0.232 or less, 0.23 or less, 0.227 or less, 0.225 or less, 0.222 0.22 or less, 0.217 or less, 0.215 or less, 0.212 or less, 0.21 or less, 0.207 or less, 0.205 or less, 0.202 or less, 0.2 or less, 0.197 or less, 0.195 or less, 0.19 2 or less, 0.19 or less, 0.187 or less, 0.185 or less, 0.182 or less, 0.18 or less, 0.177 or less, 0.175 or less, 0.172 or less, 0.17 or less, 0.167 or less, 0.165 or less, 0.162 or less, 0.16 or less, 0.155 or less, 0.152 or less, 0.15 or less, 0.147 or less, 0.145 or less, 0.142 or less, 0.14 or less, 0.137 or less, 0.135 or less, 0.132 or less, 0.13 or less, 0.127 or less, 0.125 or less, 0.122 or less, 0.12 or less, 0.117 or less, 0.115 or less, 0.112 or less, 0.11 or less, 0.107 or less, 0.105 or less, 0.102 or less, 0.1 or less, 0.095 or less, 0.09 or less, 0.085 or less, 0.08 or less, 0.075 or less, 0.07 or less, 0.065 or less, 0 It is preferable that the ratio is 0.06 or less, 0.055 or less, 0.05 or less, 0.045 or less, 0.04 or less, 0.035 or less, 0.03 or less, 0.025 or less, 0.02 or less, 0.015 or less, 0.01 or less, 0.0095 or less, 0.009 or less, 0.0085 or less, 0.008 or less, 0.0075 or less, 0.007 or less, 0.0065 or less, 0.0055 or less, 0.005 or less, 0.0045 or less, 0.004 or less, 0.0035 or less, 0.003 or less, 0.0025 or less, 0.002 or less, 0.0015 or less, or 0.001 or less.
[0033] In the general formula, the value of z is not particularly limited as long as it is within the range of 0≦z≦0.1, and may be, for example, 0.001 or more, 0.0012 or more, 0.0015 or more, 0.0017 or more, 0.002 or more, 0.0022 or more, 0.0025 or more, 0.0027 or more, 0.003 or more, 0.0032 or more, 0.0035 or more, 0.0037 or more, 0.004 or more, 0.0042 or more, above,0.0045 or more,0.0047 or more,0.005 or more,0.0052 or more,0.0055 or more,0.0057 or more,0.006 or more,0.0062 or more,0.0065 or more,0.0067 or more,0.007 or more,0.0072 or more,0.0075 or more,0.0077 or more,0.008 or more,0.0082 or more,0.0085 or more,0.0087 or more,0 .009 or more, 0.0092 or more, 0.0095 or more, 0.0097 or more, 0.01 or more, 0.012 or more, 0.015 or more, 0.017 or more, 0.02 or more, 0.022 or more, 0.025 or more, 0.027 or more, 0.03 or more, 0.032 or more, 0.035 or more, 0.037 or more, 0.04 or more, 0.042 or more, 0.045 or more, 0.047 or more, 0.0 It is preferable that the ratio is 5 or more, 0.052 or more, 0.055 or more, 0.057 or more, 0.06 or more, 0.062 or more, 0.065 or more, 0.067 or more, 0.07 or more, 0.072 or more, 0.075 or more, 0.077 or more, 0.082 or more, 0.085 or more, 0.087 or more, 0.09 or more, 0.092 or more, 0.095 or more, or 0.097 or more.On the other hand, the values of z are 0.097 or less, 0.095 or less, 0.092 or less, 0.09 or less, 0.087 or less, 0.085 or less, 0.082 or less, 0.08 or less, 0.077 or less, 0.075 or less, 0.072 or less, 0.07 or less, 0.067 or less, 0.065 or less, 0.062 or less, 0.06 or less, 0.057 or less, 0.055 or less, 0. 052 or less, 0.05 or less, 0.047 or less, 0.045 or less, 0.042 or less, 0.04 or less, 0.037 or less, 0.035 or less, 0.032 or less, 0.03 or less, 0. 027 or less, 0.025 or less, 0.022 or less, 0.02 or less, 0.017 or less, 0.015 or less, 0.012 or less, 0.01 or less, 0.0097 or less, 0.0095 or less , 0.0092 or less, 0.009 or less, 0.0087 or less, 0.0085 or less, 0.0082 or less, 0.008 or less, 0.0077 or less, 0.0075 or less, 0.0072 less than or equal to 0.007, less than or equal to 0.0067, less than or equal to 0.0065, less than or equal to 0.0062, less than or equal to 0.006, less than or equal to 0.0057, less than or equal to 0.0055, less than or equal to 0.0052, 0.00 It is preferable that the above-mentioned range is 5 or less, 0.0047 or less, 0.0045 or less, 0.0042 or less, 0.004 or less, 0.0037 or less, 0.0035 or less, 0.0032 or less, 0.003 or less, 0.0027 or less, 0.0025 or less, 0.0022 or less, 0.002 or less, 0.0017 or less, 0.0015 or less, 0.0012 or less, or 0.001 or less.
[0034] In the general formula, the element M is not particularly limited as long as it is one or more elements other than Li, Ni, Co, Mn, and O, and examples of the element M that can be used include Al, Ti, Mg, Zn, Nb, W, Mo, Sb, V, Cr, Ca, Fe, Ga, Sr, Y, Ru, In, Sn, Ta, Bi, Zr, and B. The type of element M may be selected depending on the purpose of addition. When the element M contains multiple elements, the value of w represents the total amount of the multiple elements.
[0035] In the general formula, the value of α is not particularly limited as long as it is within the range of −0.5≦α≦0.5. For example, -0.5 or more, -0.45 or more, -0.4 or more, -0.35 or more, -0.30 or more, -0.25 or more, -0.2 or more, -0.15 or more, -0.1 or more, -0.075 or more, -0.05 or more, -0.025 or more, 0.001 or more, 0.0015 or more, 0.002 or more, 0.0025 or more, 0.003 or more, 0.0035 or more, 0.004 or more, 0.0045 or more, 0.005 or more, 0.0055 or more, 0.006 or more, 0.0065 or more, 0.007 or more, 0.0075 or more, 0.008 or more, 0.0085 or more, 0.009 or more, 0.0095 or more, 0 .01 or more, 0.015 or more, 0.02 or more, 0.025 or more, 0.03 or more, 0.035 or more, 0.04 or more, 0.045 or more, 0.05 or more, 0.055 or more, 0.06 or more, 0.065 or more, 0.07 or more, 0.075 or more, 0.08 or more, 0.085 or more, 0.09 or more, 0.095 or more, 0.1 or more, 0.102 or more, 0.105 or more, 0.107 or more, 0.11 or more, 0.112 or more, 0.115 or more, 0.117 or more, 0.12 or more, 0.122 or more, 0.125 or more, 0.127 or more, 0.13 or more, 0.132 or more, 0.135 or more, 0.137 or more, 0.14 or more, 0.142 or more, 0.145 or more, 0.147 or more, 0.15 or more, 0.152 or more, 0.155 or more, 0.157 or more, 0.16 or more, 0.162 or more, 0.165 or more, 0.167 or more, 0.17 or more, 0.172 or more, 0.175 or more, 0.177 or more, 0.18 or more, 0.182 or more, 0.185 or more, 0.187 or more, 0.19 or more, 0.192 or more, 0.195 or more, 0.197 or more, 0.2 or more, 0.202 or more, 0.205 or more, 0.207 or more, 0.21 or more, 0.212 or more, 0.215 or more, 0 .217 and above, 0.22 and above, 0.222 and above, 0.225 and above, 0.227 and above, 0.23 and above, 0.232 and above, 0.235 and above, 0.237 and above, 0.24 and above, 0.242 and above, 0.245 and above, 0.247 and above, 0.25 and above, 0.252 and above, 0.255 and above, 0.257 and above, 0.26 and above, 0.262 and above, 0.265 and above, 0.267 and above, 0.27 and above, 0.272 and above, 0.275 and above, 0.277 and above, 0.28 and above, 0.282 and above, 0.285 and above, 0.287 and above, 0.29 and above, 0.292 and above, 0.295 and above, 0.297 or more, 0.3 or more, 0.302 or more, 0.305 or more, 0.307 or more, 0.31 or more, 0.312 or more, 0.315 or more, 0.317 or more, 0.32 or more, 0.322 0.325 or more, 0.327 or more, 0.33 or more, 0.332 or more, 0.335 or more, 0.337 or more, 0.34 or more, 0.342 or more, 0.345 or more, 0.347 or more Above, 0.35 or more, 0.352 or more, 0.355 or more, 0.357 or more, 0.36 or more, 0.362 or more, 0.365 or more, 0.367 or more, 0.37 or more, 0.372 or more, 0.375 or more, 0.377 or more, 0.38 or more, 0.382 or more, 0.385 or more, 0.387 or more, 0.39 or more, 0.392 or more, 0.395 or more, 0.397 or more, 0. 4 or more, 0.402 or more, 0.405 or more, 0.407 or more, 0.41 or more, 0.412 or more, 0.415 or more, 0.417 or more, 0.42 or more, 0.422 or more, 0.425 or more, 0.427 or more, 0.43 or more, 0.432 or more, 0.435 or more, 0.437 or more, 0.44 or more, 0.442 or more, 0.445 or more, 0.447 or more, 0.45 or more , 0.452 or more, 0.455 or more, 0.457 or more, 0.46 or more, 0.462 or more, 0.465 or more, 0.467 or more, 0.47 or more, 0.472 or more, 0.475 or more, 0.477 or more, 0.482 or more, 0.485 or more, 0.487 or more, 0.49 or more, 0.492 or more, 0.495 or more, 0.497 or more is preferable. On the other hand, the values of α are 0.497 or less, 0.495 or less, 0.492 or less, 0.49 or less, 0.487 or less, 0.485 or less, 0.482 or less, 0.48 or less, 0.477 or less, 0.475 or less, 0 .472 or less, 0.467 or less, 0.465 or less, 0.462 or less, 0.46 or less, 0.457 or less, 0.455 or less, 0.452 or less, 0.45 or less, 0.447 or less, 0.445 or less, 0.442 or less Below, 0.44 or less, 0.437 or less, 0.435 or less, 0.432 or less, 0.43 or less, 0.427 or less, 0.425 or less, 0.422 or less, 0.42 or less, 0.417 or less, 0.415 or less, 0.4 12 or less, 0.41 or less, 0.407 or less, 0.405 or less, 0.402 or less, 0.4 or less, 0.397 or less, 0.395 or less, 0.392 or less, 0.39 or less, 0.387 or less, 0.385 or less, 0.382 or less, 0.38 or less, 0.377 or less, 0.375 or less, 0.372 or less, 0.367 or less, 0.365 or less, 0.362 or less, 0.36 or less, 0.357 or less, 0.355 or less, 0.352 or less, 0.35 or less, 0.347 or less, 0.345 or less, 0.342 or less, 0.34 or less, 0.337 or less, 0.335 or less, 0.332 or less, 0.33 or less, 0.327 or less, 0.325 or less, 0.322 or less, 0.32 or less, 0.317 or less, 0.315 or less, 0.312 or less, 0.31 or less, 0.307 or less, 0.305 or less, 0.302 or less, 0.3 Below, 0.297 below, 0.295 below, 0.292 below, 0.29 below, 0.287 below, 0.285 below, 0.282 below, 0.28 below, 0.277 below, 0.275 below, 0.272 below, 0.27 below, 0.267 below, 0.265 below, 0.26 below, 0.257 below, 0.255 below, 0.252 below, 0.25 below, 0.247 below, 0.245 below, 0.242 below, 0.24 below, 0.237 below, 0.235 below, 0.232 below, 0.23 below, 0.227 below, 0.225 below, 0.222 below, 0.22 below, 0.217 below , 0.215 or less, 0.212 or less, 0.21 or less, 0.207 or less, 0.205 or less, 0.202 or less, 0.2 or less, 0.197 or less, 0.195 or less, 0.192 or less, 0.19 or less, 0.187 or less, 0.185 or less, 0.182 or less, 0.18 or less, 0.177 or less, 0.175 or less, 0.172 or less, 0.17 or less, 0.167 or less, 0.165 or less, 0.162 or less, 0.16 or less, 0.155 or less, 0.152 or less, 0.15 or less, 0.147 or less, 0.145 or less, 0.142 or less, 0.14 or less, 0.137 or less, 0.135 or less, 0. 132 or less, 0.13 or less, 0.127 or less, 0.125 or less, 0.122 or less, 0.12 or less, 0.117 or less, 0.115 or less, 0.112 or less, 0.11 or less, 0.107 or less, 0.105 or less, 0.102 or less, 0.1 or less, 0.095 or less, 0.09 or less, 0.085 or less, 0.08 or less, 0.075 or less, 0.07 or less, 0.065 or less, 0.06 or less, 0.055 or less, 0.05 or less, 0.045 or less, 0.04 or less, 0.035 or less, 0.03 or less, 0.025 or less, 0.02 or less, 0.015 or less, 0.01 or less, 0.0095 or less, 0.It is preferable that the molecular weight is 0.009 or less, 0.0085 or less, 0.008 or less, 0.0075 or less, 0.007 or less, 0.0065 or less, 0.006 or less, 0.0055 or less, 0.005 or less, 0.0045 or less, 0.004 or less, 0.0035 or less, 0.003 or less, 0.0025 or less, 0.002 or less, 0.0015 or less, or 0.001 or less.
[0036] The metal composite hydroxide powder has the general formula Ni 1-x-y-z Co x Mn y M z (OH) 2+α (wherein M is an element other than Li, Ni, Co, Mn, and O, and 0≦x≦0.4, 0≦y≦0.4, 0≦z≦0.1, and −0.5≦α≦0.5), and compounds other than the metal composite hydroxides represented by the same formula may be contained in an amount of, for example, 0% or more (including the case where no compounds other than the metal composite hydroxides are contained), or 10% or less, 5% or less, 2% or less, or 1% or less by mass.
[0037] The BET specific surface area of the metal composite hydroxide powder is not particularly limited, but is preferably 1 m 2 / g or more, 2m 2 / g or more, 3m 2 / g or more, 4m 2 On the other hand, the BET specific surface area of the metal composite hydroxide powder is preferably 15 m 2 / g or less, 14m 2 / g or less, 13m 2 / g or less, 12m 2 / g or less, 11m 2 / g or less, 10m 2 / g or less, 9m 2 / g or less, 8m 2 / g or less, 7m 2 / g or less, 6m 2 It is preferable that the molecular weight is not more than 1 / g.
[0038] When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of secondary particles is defined as Dt, among secondary particles having a particle diameter of Dt or more and 1.2Dt or less, in a backscattered electron image of a cross section obtained using a scanning electron microscope, primary particles having a major axis length of 1 μm or more that account for 10% or more by number are not particularly limited as long as they account for 30% or more by number, but preferably account for 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, or 80% or more.
[0039] When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of secondary particles is defined as Dt, among secondary particles having a particle diameter of Dt or more and 1.2Dt or less, in a backscattered electron image of a cross section obtained using a scanning electron microscope, it is preferable that primary particles having a major axis length of 2 μm or more account for 8% or more by number, and that these primary particles account for 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, or 80% or more by number.
[0040] The particle diameter Dt corresponding to the maximum peak top is determined by creating a volumetric particle size distribution by a wet laser method using a laser particle size distribution analyzer (Microtrac HRA, manufactured by Nikkiso Co., Ltd.) and determining the particle diameter corresponding to the maximum peak top.
[0041] The length of the primary particles of the metal composite hydroxide sample is measured as follows. First, the metal composite hydroxide sample is solidified with epoxy resin, and a cross-section of the particle is formed by an ion beam using a cross-section polisher (IB-19530CP: manufactured by JEOL Ltd.). Then, a field emission scanning electron microscope (JSM-7100F: manufactured by JEOL Ltd.) is used to take an image at an acceleration voltage of 3 kV and a magnification of 3000 to 20000 times. For the secondary particles, 100 particles are extracted that have a diameter in the range of Dt to 1.2Dt, where Dt is the particle diameter corresponding to the maximum peak top obtained by the particle size distribution measurement based on the volume.
[0042] Among the secondary particles in the electron microscope photographs of the backscattered electron images obtained, the grain boundaries of the primary particles within the secondary particles are depicted for all particles in which the outlines of the primary particles can be confirmed using Paint, which is an accessory to Microsoft Windows, and the images of the grain boundaries are binarized using image processing software (e.g., ImageJ, etc.) to calculate the particle length in the major axis direction. From the obtained data on the particle lengths in the major axis direction, a kernel density distribution (number basis) is calculated using the standard normal distribution as the kernel function.
[0043] The pore volume of the metal composite hydroxide powder having a pore diameter of 0.06 μm or less is not particularly limited as long as it is 0.15 mL / g or less, but is preferably 0.14 mL / g or less, 0.13 mL / g or less, 0.12 mL / g or less, 0.11 mL / g or less, or 0.10 mL / g or less. The pore volume of the metal composite hydroxide powder having a pore diameter of 0.06 μm or less is preferably 0 mL / g or more, 0.01 mL / g or more, or 0.02 mL / g or more.
[0044] The tap density of the metal composite hydroxide powder is not particularly limited, but is preferably, for example, 1 g / cc or more, 1.1 g / cc or more, 1.2 g / cc or more, 1.3 g / cc or more, 1.4 g / cc or more, 1.5 g / cc or more, 1.6 g / cc or more, 1.7 g / cc or more, 1.8 g / cc or more, or 1.9 g / cc or more. On the other hand, the tap density of the metal composite hydroxide powder is not particularly limited, but is preferably, for example, 4 g / cc or less, 3.5 g / cc or less, 3 g / cc or less, 2.7 g / cc or less, 2.5 g / cc or less, 2.4 g / cc or less, or 2.3 g / cc or less.
[0045] In the X-ray diffraction pattern of the metal composite hydroxide powder obtained by X-ray diffraction measurement, the full width at half maximum (FWHM) of the (001) plane is not particularly limited, but is preferably 0.2° or more, 0.25° or more, or 0.3° or more. On the other hand, the full width at half maximum (FWHM) of the (001) plane is preferably 0.7° or less, 0.65° or less, 0.6° or less, 0.55° or less, 0.5° or less, 0.45° or less, 0.4° or less, 0.39° or less, 0.38° or less, 0.37° or less, 0.36° or less, or 0.35° or less.
[0046] In the X-ray diffraction pattern of the metal composite hydroxide powder obtained by X-ray diffraction measurement, the full width at half maximum (FWHM) of the (100) plane is not particularly limited, but is preferably 0.3° or more, 0.35° or more, or 0.4° or more. On the other hand, the full width at half maximum (FWHM) of the (100) plane is preferably 0.75° or less, 0.7° or less, 0.69° or less, 0.68° or less, 0.67° or less, 0.66° or less, or 0.65° or less.
[0047] In the X-ray diffraction pattern of the metal composite hydroxide powder obtained by X-ray diffraction measurement, the full width at half maximum (FWHM) of the (101) plane is not particularly limited, but is preferably 0.5° or more, 0.55° or more, 0.6° or more, or 0.65° or more. On the other hand, the full width at half maximum (FWHM) of the (101) plane is preferably 1.5° or less, 1.4° or less, 1.3° or less, 1.2° or less, 1.1° or less, 1.0° or less, 0.97° or less, 0.95° or less, or 0.9° or less.
[0048] (Method of manufacturing metal composite hydroxide powder) The method for producing the metal composite hydroxide powder will be described below.
[0049] The method for producing the metal composite hydroxide powder is not particularly limited, but for example, a method can be used in which an aqueous solution containing various aqueous solutions of compounds containing metal elements and other elements according to the composition of the composite oxide to be produced is dropped into a reaction tank in which an aqueous alkali solution such as an aqueous sodium hydroxide solution or an ammonia solution is stirred as a mother liquid, and while also dropping sodium hydroxide, etc., the pH is monitored and controlled to be in an appropriate range, and co-precipitation is performed by a wet reaction to obtain the powder. Note that even if the metal composite hydroxide powder is produced by a method other than this method, the problem of the present disclosure can be solved as long as it has the above-mentioned configuration.
[0050] In the production of the metal composite hydroxide powder, it is preferable to introduce an inert gas (industrially preferably nitrogen gas) into the reaction tank to create a nitrogen atmosphere in the reaction tank after preparing the alkaline aqueous solution as the mother liquid, and to reduce the oxygen concentration in the reaction tank system and in the solution as much as possible. If the oxygen concentration is too high, the coprecipitated hydroxide may be over-oxidized by a predetermined amount or more of remaining oxygen, or the formation of aggregates due to crystallization may be hindered.
[0051] The aqueous solution of the element as the source of the element constituting the metal composite hydroxide powder is not particularly limited, but for example, an acidic aqueous solution is preferably used, and an aqueous sulfuric acid solution is more preferably used. One or more kinds of aqueous solutions of the element can be used.
[0052] The element source is not particularly limited as long as the type and stoichiometric ratio of the elements are adjusted according to the composition contained in the lithium metal oxide to be produced. Compounds of each element that can be used as the element source will be described below.
[0053] The nickel compound is not particularly limited, but for example, one or more selected from nickel sulfate, nickel oxide, nickel hydroxide, nickel nitrate, nickel carbonate, nickel chloride, nickel iodide, and metallic nickel can be used.
[0054] The cobalt compound is not particularly limited, but for example, one or more selected from cobalt sulfate, cobalt oxide, cobalt hydroxide, cobalt nitrate, cobalt carbonate, cobalt chloride, cobalt iodide, and metallic cobalt can be used.
[0055] The manganese compound is not particularly limited, but for example, one or more selected from manganese sulfate, manganese oxide, manganese hydroxide, manganese nitrate, manganese carbonate, manganese chloride, manganese iodide, and manganese metal can be used.
[0056] The aluminum compound is not particularly limited, but for example, one or more selected from aluminum sulfate, aluminum oxide, aluminum hydroxide, aluminum nitrate, aluminum carbonate, aluminum chloride, aluminum iodide, sodium aluminate, metallic aluminum, and the like can be used.
[0057] The titanium compound is not particularly limited, but for example, one or more selected from titanyl sulfate, titanium oxide, titanium hydroxide, titanium nitrate, titanium carbonate, titanium chloride, titanium iodide, and metallic titanium can be used.
[0058] The iron compound is not particularly limited, but for example, one or more selected from iron sulfate, iron oxide, iron hydroxide, iron nitrate, iron carbonate, iron chloride, iron iodide, metallic iron, and the like can be used.
[0059] The niobium compound is not particularly limited, but for example, one or more selected from niobium oxide, niobium chloride, lithium niobate, niobium iodide, and the like can be used.
[0060] The tungsten compound is not particularly limited, but for example, one or more compounds selected from tungsten oxide, sodium tungstate, ammonium paratungstate, tungsten hexacarbonyl, tungsten sulfide, and the like can be used.
[0061] The magnesium compound is not particularly limited, but for example, one or more types selected from magnesium sulfate, magnesium oxide, magnesium hydroxide, magnesium nitrate, magnesium carbonate, magnesium chloride, magnesium iodide, and metallic magnesium can be used.
[0062] The zinc compound is not particularly limited, but for example, one or more selected from zinc sulfate, zinc oxide, zinc hydroxide, zinc nitrate, zinc carbonate, zinc chloride, zinc iodide, and zinc metal can be used.
[0063] As for the other elements, one or more selected from sulfates, oxides, hydroxides, nitrates, carbonates, chlorides, iodides, metals, and the like can be used.
[0064] The mixing ratio of each compound may be adjusted by adjusting the amount of each element depending on the composition of the lithium metal composite oxide to be produced.
[0065] The appropriate pH range for producing the metal composite hydroxide powder is not particularly limited and may be determined so as to obtain the secondary particle size and shape such as the degree of coarseness and density to be produced. Generally, the range is about 10 to 13.
[0066] The metal composite hydroxide powder obtained by the wet reaction is preferably subjected to a washing treatment, dehydrated, and then dried.
[0067] By subjecting the metal composite hydroxide powder to a washing treatment, it is possible to wash away impurities such as sulfate radicals, carbonate radicals, and sodium that are incorporated into the aggregated particles during the reaction or that are attached to the surface layer. For the washing treatment, a Nutsche washing method using a Buchner funnel can be used if the amount is small, or a method in which the suspension after the reaction is sent to a press filter for washing and dehydration can be used. In addition, for example, pure water, an aqueous sodium hydroxide solution, an aqueous sodium carbonate solution, etc. can be used in the washing treatment, but it is preferable to use pure water from an industrial perspective. However, if there is a large amount of residual sulfate radicals, an aqueous sodium hydroxide solution with a pH controlled according to the amount of residual sulfate radicals may be used.
[0068] (2) Calcination process The calcination step is a step of calcining the metal composite hydroxide powder. Note that the calcination step is not an essential step in the method for producing a lithium metal composite oxide according to the embodiment of the present disclosure.
[0069] In this way, by calcining the metal composite hydroxide powder before mixing it with the lithium compound, the metal composite hydroxide powder can be decarbonated and dehydrated.
[0070] The calcination conditions are not particularly limited, but it is preferable to perform the calcination under an oxidizing atmosphere at a heating temperature of 200 to 700°C for a heating time of 1 to 6 hours. The heating temperature is the temperature of the part having the highest temperature in the metal composite hydroxide powder, and the heating time is the time during which the temperature of the part having the highest temperature is maintained within the above-mentioned temperature range. By passing through the calcination, it is possible to appropriately remove impurities remaining in the metal composite hydroxide powder, and a calcined product can be obtained. The heating temperature is the temperature of the part having the highest temperature when the heated object is heated and raised, and the heating time is the time during which the temperature of the part having the highest temperature in the heated object is maintained within the above-mentioned temperature range (the same applies to the following steps).
[0071] [(3) Mixing process] A mixture is prepared by mixing the composite metal hydroxide powder prepared in the precursor preparation step and / or the calcined product prepared in the calcination step with a lithium source in a predetermined ratio. The mixing method is not particularly limited, but may be, for example, a method in which the powder of the metal composite hydroxide and / or the calcined product and the powder of a lithium compound as the lithium source are weighed out to a predetermined ratio and mixed in a dry state, or a method in which the metal composite hydroxide and / or the calcined product and an aqueous solution of the lithium source are mixed in a predetermined ratio and the entire amount of the suspension obtained is dried. Note that the mixing step is not an essential step in the method for producing a lithium metal composite oxide according to the embodiment of the present disclosure.
[0072] The lithium compound is not particularly limited, and various lithium salts can be used.Specifically, the lithium compound can be one or more selected from anhydrous lithium hydroxide, lithium hydroxide hydrate, lithium nitrate, lithium carbonate, lithium acetate, lithium bromide, lithium chloride, lithium citrate, lithium fluoride, lithium iodide, lithium lactate, lithium oxalate, lithium phosphate, lithium pyruvate, lithium sulfate, and lithium oxide.Among these, it is preferable to use one or more selected from anhydrous lithium hydroxide and lithium hydroxide hydrate.
[0073] The blending ratio of the metal composite hydroxide powder and / or the calcined product to the lithium source is not particularly limited, and may be adjusted so that the total amount of each element is a desired ratio depending on the composition of the lithium metal composite oxide to be produced.
[0074] (4) Firing process The calcination step is a step of calcining a mixture of a metal composite hydroxide powder and / or a metal composite compound and a lithium source at 700° C. or more and 950° C. or less.
[0075] In the calcination for producing a lithium metal composite oxide containing at least nickel, a lithiation reaction and crystal growth take place. Of these, the lithiation reaction requires a certain oxygen partial pressure. The lithiation reaction causes the metal composite hydroxide as a raw material to be lithiated, and a lithium metal composite oxide is obtained. Thereafter, the temperature is raised to a predetermined temperature, which promotes the crystal growth of the lithium metal composite oxide.
[0076] The heating temperature in the firing is not particularly limited, but is preferably 700 to 950° C., 700 to 930° C., or 710 to 900° C. The firing time is preferably, for example, 1 to 24 hours, 1 to 20 hours, 1 to 15 hours, 1 to 10 hours, 2 to 9 hours, or 3 to 8 hours.
[0077] (Pre-baking) In general, the calcination is carried out by filling a mixture obtained by mixing a metal composite hydroxide powder and / or a composite metal compound with a lithium source in a mixer in a container such as a crucible or a sagger. In particular, in the lithiation reaction, it becomes difficult to exhaust the generated gas to the outside and to diffuse the required oxygen concentration as the mixed powder approaches the bottom of the container. As a result, it may become difficult to control the uniformity of the reaction and the primary particle size.
[0078] Therefore, when producing the lithium metal composite oxide according to the embodiment of the present disclosure, it is preferable to use a two-stage calcination method in which pre-calcination is performed under the following specified conditions, and then main calcination is performed under the following specified conditions, although the pre-calcination is not an essential step.
[0079] In this pre-baking, it is preferable to adopt a baking method that accelerates the lithiation reaction. Specifically, a method is exemplified in which the mixture is made more susceptible to heat, gas generated from the lithium source is easily discharged, and gas with a high oxygen partial pressure is diffused into the mixture (particles). For example, it is possible to achieve the desired characteristics by pre-baking a smaller amount of the mixture or pre-baking while flowing.
[0080] For pre-firing of the mixture, the mixture can be filled into a sagger or crucible and fired using a stationary furnace, roller hearth kiln, pusher furnace, or the like, but a rotary kiln in which the mixture is fired while being fluidized can also be used.
[0081] The heating temperature in the preliminary calcination is not particularly limited as long as it is lower than the heating temperature in the main calcination described below, and is preferably adjusted according to the type of lithium compound used in the preparation of the mixture. This ensures that the metal composite hydroxide and / or composite metal compound in the mixture reacts with the lithium compound, ensures that the lithiation reaction proceeds uniformly and without the generation of heterogeneous phases, and allows the desired lithium metal composite oxide to be obtained.
[0082] The atmosphere for the preliminary firing is not particularly limited, and may be an oxidizing atmosphere in which the lithiation reaction proceeds reliably and uniformly. For example, it is preferable to use air (oxygen concentration: 21 vol%), a decarbonated oxidizing gas atmosphere with a carbon dioxide gas concentration of 30 ppm or less, or an oxygen atmosphere with an oxygen concentration of 80 vol% or more, 90 vol% or more.
[0083] The pre-baking time is not particularly limited as long as the lithium addition reaction proceeds reliably and uniformly, and is preferably 1 to 10 hours, more preferably 2 to 8 hours.
[0084] (Final firing) The pre-calcined mixture is then subjected to a main calcination at a higher temperature in order to promote crystal growth and particle growth. At this time, it is necessary to ensure that the crystal growth proceeds uniformly to obtain a lithium metal composite oxide having a desired crystal structure.
[0085] The atmosphere for the main firing is not particularly limited, and may be any atmosphere that ensures reliable and uniform crystal growth, has an oxygen partial pressure that does not reduce the transition metal contained in the mixture to be fired, and preferably has a low moisture content and carbon dioxide gas concentration. For example, it is preferable to use air (oxygen concentration: 21 vol%), a decarbonated oxidizing gas atmosphere with a carbon dioxide gas concentration of 30 ppm or less, or an oxygen atmosphere with an oxygen concentration of preferably 80 vol% or more, 90 vol% or more.
[0086] The temperature of the main firing is not particularly limited as long as it is higher than the temperature of the preliminary firing, and can be adjusted according to the composition of the lithium metal composite oxide to be obtained. For example, it is preferable to adjust the maximum temperature to 700 to 950°C, 700 to 930°C, or 710 to 900°C. By setting the maximum temperature within the required range, it is possible to obtain a lithium metal composite oxide having a desired crystal structure with a reduced amount of unreacted components, and it is also possible to prevent a decrease in the battery characteristics of a non-aqueous electrolyte secondary battery using the obtained lithium metal composite oxide as a positive electrode. In addition, when obtaining a lithium metal composite oxide with a Ni content of 20 to 80 mol% in elements other than Li, it is preferable to fire the mixture at a maximum temperature not exceeding 950°C.
[0087] The time for the main baking is not particularly limited as long as it is long enough to form a lithium metal composite oxide having a desired crystal structure, and is preferably 1 to 15 hours, 2 to 12 hours, or 2 to 10 hours.
[0088] (5) Cleaning process The washing step is a step of washing the lithium metal composite oxide obtained by firing in the firing step with water, although the washing step is not an essential step.
[0089] The lithium metal composite oxide obtained in the calcination process may contain impurities such as unreacted lithium compounds and lithium compounds that appear on the particle surface due to the crystal structure during the calcination process. Therefore, in order to remove or reduce these impurities, the product may be washed with water and heat-treated, for example.
[0090] (6) Surface treatment process The surface treatment step is a step of subjecting the lithium metal composite oxide obtained in the firing step or the washing step to a surface treatment, although the surface treatment step is not an essential step.
[0091] By adding and mixing a specified element compound to the composite oxide obtained in the firing step or washing step and subjecting it to heat treatment, the surfaces of the primary particles and / or secondary particles of the lithium metal composite oxide can be surface-treated with a compound of lithium and the added element, thereby obtaining effects such as reducing the amount of lithium compounds remaining on the particle surface, improving lithium ion conductivity, and reducing reaction resistance.
[0092] The element compound added for the above-mentioned surface treatment can be selected from, for example, aluminum compounds, boron compounds, tungsten compounds, manganese compounds, cobalt compounds, phosphorus compounds, niobium compounds, strontium compounds, antimony compounds, zirconium compounds, titanium compounds, and the like, and one or more of them can be used.
[0093] The lithium metal composite oxide produced by the above steps is, for example, represented by the general formula Li a Ni 1-x-y-z Co x Mn y M z O 2+α (wherein M is one or more elements other than Li, Ni, Co, Mn, and O, and 0.90≦a≦1.15, 0≦x≦0.4, 0≦y≦0.4, 0≦z≦0.1, −0.5≦α≦0.5). Note that the values of x, y, and z and the type of element M are the same as those of the above-mentioned metal composite hydroxide, and therefore description thereof will be omitted here.
[0094] In the general formula, the value of a is not particularly limited as long as it is within the range of 0.90≦a≦1.15, and may be, for example, 0.905 or more, 0.91 or more, 0.915 or more, 0.92 or more, 0.925 or more, 0.93 or more, 0.935 or more, 0.94 or more, 0.945 or more, 0.95 or more, 0.955 or more, 0.96 or more, 0.965 or more, 0.97 or more, 0.975 or more, 0.98 or more, 0.985 or more, 0.99 or more, 0.995 or more, 1 or more, 1.005 or more, 1.01 or more, 1.015 or more, It is preferable that the above-mentioned range is 1.02 or more, 1.025 or more, 1.03 or more, 1.035 or more, 1.04 or more, 1.045 or more, 1.05 or more, 1.055 or more, 1.06 or more, 1.065 or more, 1.07 or more, 1.075 or more, 1.08 or more, 1.085 or more, 1.09 or more, 1.095 or more, 1.1 or more, 1.105 or more, 1.11 or more, 1.115 or more, 1.12 or more, 1.125 or more, 1.13 or more, 1.135 or more, 1.14 or more, 1.145 or more, or 1.15 or more. On the other hand, the value of a is 1.15 or less, 1.145 or less, 1.14 or less, 1.135 or less, 1.13 or less, 1.125 or less, 1.12 or less, 1.115 or less, 1.11 or less, 1.105 or less, 1.1 or less, 1.095 or less, 1.09 or less, 1.085 or less, 1.08 or less, 1.075 or less, 1.07 or less, 1.065 or less, 1.06 or less, 1.055 or less, 1.05 or less, 1.045 or less, 1.04 or less, 1.035 or less, 1.03 or less , 1.025 or less, 1.02 or less, 1.015 or less, 1.01 or less, 1.005 or less, 1 or less, 0.995 or less, 0.99 or less, 0.985 or less, 0.98 or less, 0.975 or less, 0.97 or less, 0.965 or less, 0.96 or less, 0.955 or less, 0.95 or less, 0.945 or less, 0.94 or less, 0.935 or less, 0.93 or less, 0.925 or less, 0.92 or less, 0.915 or less, 0.91 or less, 0.905 or less.
[0095] ≪Nonaqueous electrolyte secondary battery≫ The lithium metal composite oxide produced by the production method according to the embodiment of the present disclosure can be used as a positive electrode active material for a non-aqueous electrolyte secondary battery. Here, a non-aqueous electrolyte secondary battery using a lithium metal composite oxide will be described. This non-aqueous electrolyte secondary battery is provided with a positive electrode containing the above-mentioned lithium metal composite oxide as a positive electrode active material, and the non-aqueous electrolyte secondary battery is composed of a positive electrode, a negative electrode, and an electrolyte-containing electrolytic solution.
[0096] When manufacturing the positive electrode, a conductive agent and a binder are added to the lithium metal composite oxide according to the embodiment of the present disclosure and mixed according to a conventional method. As the conductive agent, for example, acetylene black, carbon black, graphite, etc. are preferably used. As the binder, for example, polytetrafluoroethylene, polyvinylidene fluoride, etc. are preferably used.
[0097] The negative electrode is not particularly limited, but may be, for example, not only a negative electrode active material such as lithium metal, graphite, or a low-crystalline carbon material, but also one or more nonmetallic or metallic elements selected from Si, Al, Sn, Pb, Zn, Bi, and Cd, an alloy containing the same, or a chalcogen compound containing the same.
[0098] The solvent for the electrolyte is not particularly limited, but may be, for example, an organic solvent containing one or more selected from carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate, and ethers such as dimethoxyethane.
[0099] As the electrolyte, in addition to lithium hexafluorophosphate (LiPF6), one or more selected from lithium salts such as lithium perchlorate and lithium tetrafluoroborate can be dissolved in a solvent and used. EXAMPLES
[0100] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.
[0101] <Sample preparation> Samples of Examples 1 and 2 and Comparative Example 1 were prepared according to the methods described below.
[0102] Example 1 (Nucleation stage) A nickel sulfate aqueous solution, a cobalt sulfate aqueous solution, and a manganese sulfate aqueous solution were mixed so that the ratio (molar ratio) of Ni, Co, and Mn was Ni:Co:Mn=55:20:25 to obtain a mixed aqueous solution. 10 L of pure water was added to the reaction vessel, and 200 g of ammonia water was added. Sodium hydroxide solution was then added so that the pH was 12 to prepare a reaction mother liquid. Nitrogen gas was purged into the reaction vessel at a flow rate of 0.7 L / min to create a nitrogen atmosphere in the reaction vessel. The nitrogen atmosphere was maintained until the end of the reaction. The solution in the reaction vessel was stirred, and the prepared mixed aqueous solution was added dropwise to prepare a liquid medium containing seed crystals.
[0103] (Crystallization stage) After the seed generation stage, sodium hydroxide, ammonia water, and the mixed solution were added to the reactor in a specified ratio to carry out the crystallization reaction. During the reaction, the volume of the reactor was controlled to be constant. During the crystallization stage, the pH in the reactor was controlled to be constantly maintained at 11.7.
[0104] During the reaction, samples were taken over time to measure the particle size distribution and BET specific surface area to confirm that no secondary nuclei (seed nuclei) were generated. The rate at which the raw materials were dropped was kept constant, and the reaction was carried out so that the average particle diameter D50 was 17 μm.
[0105] After the dropping of the raw materials was completed, the mixture was stirred for 1 hour to obtain a coprecipitate in which Ni, Co, and Mn crystallized to form aggregated particles. The slurry in the reactor was then washed with pure water using a Buchner funnel to reduce residual impurities, followed by solid-liquid separation. The coprecipitate cake was dried at 110°C for 12 hours in an air environment to obtain a metal composite hydroxide sample. The volume-based average particle size D50 of the obtained metal composite hydroxide was 16.6 μm.
[0106] The metal composite hydroxide obtained as described above was subjected to a calcination process in which it was heat-treated at 300°C for 4 hours in an air environment to obtain a metal composite compound. The obtained metal composite compound, lithium carbonate, and zirconium oxide were weighed and mixed so that the lithium metal composite oxide finally produced had Li / (Ni+Co+Mn)=1.035 and Zr / (Ni+Co+Mn+Zr)=0.45 mol%. After that, the mixture was heat-treated at 780°C for 3 hours in an air environment (oxygen concentration: 21 vol%), and then calcined at 880°C for 6 hours in an air environment (oxygen concentration: 21 vol%). The calcined product obtained was pulverized to obtain a lithium nickel composite oxide.
[0107] Boric acid powder was added to and mixed with the obtained lithium metal composite oxide so that the amount of B in the final lithium metal composite oxide sample was 1000 ppm, and the mixture was heat-treated at 350°C for 2 hours in an oxygen atmosphere (oxygen concentration: 92 vol%) to obtain a positive electrode active material sample.
[0108] Example 2 In Example 1, in the crystallization stage, the pH in the reaction tank was controlled to be constantly maintained at 11.5 during the crystallization stage. In addition, by sampling over time during the reaction and measuring the particle size distribution and BET specific surface area, it was confirmed that secondary nuclei (seed nuclei) were not generated. The dropping speed was gradually reduced with the growth of the particle size by checking the surface morphology with an SEM image, and was finally set to 1 / 5 of the speed at the start of dropping. The reaction was carried out so that the average particle diameter D50 was 17 μm. A lithium metal composite oxide sample was obtained in the same manner as in Example 1 except for the above points. The average particle diameter D50 on a volume basis of the obtained metal composite hydroxide was 17.0 μm.
[0109] The metal composite hydroxide obtained as described above was subjected to a calcination step in which the metal composite hydroxide was heat-treated at 300° C. for 4 hours in an atmospheric environment to obtain a metal composite compound. A composite oxide sample of Example 2 was obtained in the same manner as in Example 1, except that the obtained metal composite compound, lithium carbonate, and zirconium oxide were weighed and mixed so that the final positive electrode active material had Li / (Ni+Co+Mn)=1.050 and Zr / (Ni+Co+Mn+Zr)=0.45 mol%.
[0110] Comparative Example 1 A metal composite hydroxide sample was obtained in the same manner as in Example 1, except that the pH was increased by 0.25 and the raw material dropping rate was increased stepwise in the crystallization stage in Example 1. The volume-based average particle diameter D50 of the obtained metal composite hydroxide was 16.2 μm.
[0111] The subsequent operations were carried out in the same manner as in Example 1 to obtain a lithium metal composite oxide.
[0112] <Evaluation> The samples of Examples 1 and 2 and Comparative Example 1 were evaluated by the methods described below.
[0113] [Composition analysis of metal composite hydroxide sample and lithium metal composite oxide sample] The composition of the metal composite hydroxide sample and the lithium metal composite oxide sample was determined by the following method. 0.2 g of each sample was dissolved by heating in 25 ml of 20% hydrochloric acid solution, cooled, transferred to a 100 ml measuring flask, and pure water was added to prepare an adjusted solution. The elements of the obtained adjusted solution were quantified using ICP-AES (Optima 8300, manufactured by PerkinElmer Japan Co., Ltd.).
[0114] [Tap density of metal composite hydroxide sample] The tap density was measured by tapping 500 times using a tap denser.
[0115] [Particle diameter (Dt) corresponding to the maximum peak top of the metal complex hydroxide sample] The particle diameter Dt corresponding to the maximum peak top was determined by creating a volumetric particle size distribution by a wet laser method using a laser particle size distribution analyzer (Microtrac HRA, manufactured by Nikkiso Co., Ltd.) and determining the particle diameter corresponding to the maximum peak top.
[0116] [Full width at half maximum (FWHM) by XRD diffraction of metal complex hydroxide sample] Using an X-ray diffractometer [SmartLab, Rigaku Corporation], XRD diffraction data of the metal complex hydroxide sample was obtained under the following X-ray diffraction conditions, and then the XRD diffraction data was used to perform Rietveld analysis with reference to "RA Young, ed., "The Rietveld Method", Oxford University Press (1992)". At this time, for the FWHM (full width at half maximum), the values at the (001) peak, (100) peak, and (101) peak were used when the obtained XRD diffraction was indexed as space group: P-3m1. (X-ray diffraction conditions) Source: Cu-Kα Acceleration voltage and current: 45kV and 200mA Sampling width: 0.02 deg. Scanning width: 5deg.~80deg. Scan speed: 1.0 step / sec Divergence slit: 2 / 3deg. Receiving slit width: 0.15 mm Scattering slit: 2 / 3deg.
[0117] [Measurement of pore distribution of metal composite hydroxide samples] The pore size distribution of the metal composite hydroxide sample was measured by mercury intrusion porosimetry using an Autopore V9620 (Micromeritics). The measurement method is as follows. (Mercury porosimetry conditions) Pretreatment: No pretreatment. Measurement: The pore distribution was determined with a pore diameter of approximately 0.0036 to 200 μm. The pore size was calculated using the Washburn formula shown below. PD=-4σcosθ (In the formula, P: pressure, σ: surface tension of mercury, D: pore diameter, θ: contact angle between mercury and sample) (Measurement conditions) Surface tension of mercury: 480 dynes / cm Contact angle between mercury and sample: 140 deg.
[0118] [Method for measuring the length of primary particles of a metal composite hydroxide sample] The length of the primary particles of the metal composite hydroxide sample was measured as follows. First, the metal composite hydroxide sample was solidified with epoxy resin, and a particle cross section was formed by an ion beam using a cross-section polisher (IB-19530CP, manufactured by JEOL Ltd.). Then, a field emission scanning electron microscope (JSM-7100F, manufactured by JEOL Ltd.) was used to take images at an acceleration voltage of 3 kV and a magnification of 3000 to 20000 times. For the secondary particles, 100 particles were extracted from the range of the diameter of the secondary particles Dt to 1.2Dt, where Dt is the particle diameter corresponding to the maximum peak top obtained by the particle size distribution measurement based on the volume.
[0119] Among the secondary particles in the electron microscope photographs of the backscattered electron images obtained, the grain boundaries of the primary particles within the secondary particles were depicted for all particles in which the outlines of the primary particles could be confirmed using Paint, which is an accessory of Microsoft Windows, and the images of the grain boundaries were binarized using image processing software (e.g., ImageJ, etc.) to calculate the length of the particles in the major axis direction. From the obtained data on the length of the particles in the major axis direction, a kernel density distribution (number basis) was calculated using the standard normal distribution as the kernel function.
[0120] [Evaluation using coin cells with positive electrode active material samples] A 2032 type coin cell using positive electrode active material particles obtained by lithiating a lithium metal composite oxide was manufactured using a positive electrode, a negative electrode, and an electrolyte prepared by the following methods.
[0121] (positive electrode) Acetylene black and graphite were used as conductive agents in a ratio of 1:1 (weight ratio), and polyvinylidene fluoride was used as a binder. The positive electrode active material, conductive agent, and binder were mixed in a ratio of 90:6:4 (weight ratio) of positive electrode active material:conductive agent:binder, and these were mixed with N-methylpyrrolidone and applied to an aluminum foil. This was dried at 110°C to prepare a sheet, which was then punched out to a diameter of 15 mm and then cut into 3 t / cm. 2 The resultant was rolled at 100° C. to prepare a positive electrode.
[0122] (Negative electrode) A lithium foil having a thickness of 500 μm and punched to 16 mmφ was used as the negative electrode.
[0123] (electrolyte) A mixed solvent of EC and DMC was prepared so that the volume ratio of EC:DMC was 1:2, and a solution obtained by mixing the electrolyte with 1 mol / L of LiPF6 was used as the electrolyte solution.
[0124] (Separator) A separator (Celgard#2400, manufactured by Celgard) having a thickness of 0.5 mm and punched out to 20 mm in diameter was used.
[0125] (1) Initial charge capacity and initial charge / discharge efficiency Using the coin cell manufactured by the above-mentioned method, in an environment of 25° C., constant current charging was performed at a current density of 0.2 C up to 4.35 V (upper limit voltage), and then constant voltage charging was performed until the current became 0.05 C. The capacity at this time was defined as the initial charge capacity (mAh / g).
[0126] Next, after a 10-minute pause, constant-current discharge was performed at a current density of 0.1 C to 2.50 V under the same environment, and after a 10-minute pause, the initial discharge capacity (mAh / g) was measured.
[0127] The initial charge / discharge efficiency was calculated based on the measured initial charge capacity and the measured initial discharge capacity according to the following formula. Initial charge / discharge efficiency (%) = (initial discharge capacity / initial charge capacity) x 100
[0128] (2) Cycle maintenance rate The coin cell manufactured by the above-mentioned method was subjected to 104 charge / discharge cycles in an environment of 60° C. under the conditions shown below. Cycles 1, 2 and 104: Charge at 0.2C constant current until 4.3V, then charge at 0.01C constant voltage 5 minute pause 0.2C constant current discharge to 3.0V 5 minute pause Cycles 3 to 103: Charge at 0.5C constant current until 4.3V, then charge at 0.01C constant voltage 5 minute pause 1C constant current discharge to 3.0V 5 minute pause Using the measured value of the discharge capacity at the 30th cycle and the measured value of the discharge capacity at the 103rd cycle, the cycle retention rate at 60° C. was calculated according to the following formula. Cycle maintenance rate (%) = (discharge capacity at 103rd cycle / discharge capacity at 30th cycle) x 100
[0129] The evaluation results are shown in Table 1.
[0130] [Table 1]
Claims
1. The method includes a step of calcining a mixture of a metal composite hydroxide powder and a lithium source at 700° C. or more and 950° C. or less, The metal composite hydroxide powder contains at least nickel and includes secondary particles formed by aggregation of primary particles, When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more by number of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more that account for 10% or more by number in a backscattered electron image of a cross section obtained using a scanning electron microscope, The pore volume of the pores having a diameter of 0.06 μm or less is 0.15 mL / g or less. A method for producing a lithium metal composite oxide.
2. A step of calcining the metal composite hydroxide powder at 200° C. or more and less than 700° C. to obtain a calcined product; and firing the mixture of the calcined product and the lithium source at a temperature of 700° C. or higher and 950° C. or lower. The metal composite hydroxide powder contains at least nickel and includes secondary particles formed by aggregation of primary particles, When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more by number of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more that account for 10% or more by number in a backscattered electron image of a cross section obtained using a scanning electron microscope, The pore volume of the pores having a diameter of 0.06 μm or less is 0.15 mL / g or less. A method for producing a lithium metal composite oxide.
3. The metal composite hydroxide powder has the general formula Ni 1-x-y-z Co x Mn y M z (OH) 2+α (wherein M is an element other than Li, Ni, Co, Mn, and O, and 0≦x≦0.4, 0≦y≦0.4, 0≦z≦0.1, and −0.5≦α≦0.5) The method for producing the lithium metal composite oxide according to claim 1 or 2.
4. Of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less, 30% or more by number are primary particles having a major axis length of 2 μm or more in a backscattered electron image of a cross section obtained using a scanning electron microscope, and 8% or more by number are primary particles. The method for producing the lithium metal composite oxide according to claim 1 or 2.
5. The BET specific surface area of the metal composite hydroxide powder is 1 m 2 / g or more 15m 2 / g or less The method for producing the lithium metal composite oxide according to claim 1 or 2.
6. The composition contains at least nickel and secondary particles formed by agglomeration of primary particles, When the particle diameter corresponding to the maximum peak top of the volume-based particle diameter frequency distribution of the secondary particles is defined as Dt, 30% or more by number of the secondary particles having a particle diameter of Dt or more and 1.2Dt or less are primary particles having a major axis length of 1 μm or more that account for 10% or more by number in a backscattered electron image of a cross section obtained using a scanning electron microscope, The pore volume of the pores having a diameter of 0.06 μm or less is 0.15 mL / g or less. Metal composite hydroxide powder.
Citation Information
Patent Citations
Electrode for nonaqueous secondary battery and nonaqueous secondary battery
JP2011023335A